Drivers That Influence Employee Engagement : Sarawak Timber Industry Development Corporation (STIDC) / Mulyadi Mohamad… [et al.] - Mohamad, Mulyadi; Jion, Ernest; Edward, Stephannie Ruwi (2012)
The purpose of this research is to gain a better comprehension of the drivers that can influence the employee engagement in STIDC. This study was conducted for 132 staffs in STIDC Kuching Sarawak. Important statistical data were obtained from questionnaires distributed and analyzed using Statistical Package for Social Science (SPSS) version 19. After thorough examination, it is found that there is a significant relationship between the three independent variables namely Employee Communication, Rewards and Recognition and Employee Development with the dependent variables - Employee Engagement. Of those three" independent variables, reward and recognition has been identified to be the most essential independent variable to drive the employee engagement level in STIDC.